Investigation of Dissolution Mechanism and Release Kinetics of Poorly Water-Soluble Tadalafil from Amorphous Solid Dispersions Prepared by Various Methods - Školáková, Tereza; Slámová, Michaela; Školáková, Andrea; Kadeřábková, Alena; Patera, Jan; Zámostný, Petr (Pharmaceutics, 2019)
The aims of this study were to investigate how the release of tadalafil is influenced by two grades of polyvinylpyrrolidone (Kollidon® 12 PF and Kollidon® VA 64) and various methods of preparing solid dispersions (solvent evaporation, spray drying and hot-melt extrusion). Tadalafil is poorly water-soluble and its high melting point makes it very sensitive to the solid dispersion preparation method. Therefore, the objectives were to make a comparative evaluation among different solid dispersions and to assess the effect of the physicochemical nature of solid dispersions on the drug release profile with respect to the erosion-diffusion mechanism. The solid dispersions were evaluated for dissolution profiles, XRD, SEM, FT-IR, DSC, and solubility or stability studies. It was found that tadalafil release was influenced by polymer molecular weight. Therefore, solid dispersions containing Kollidon® 12 PF showed a faster dissolution rate compared to Kollidon® VA 64. Tadalafil was released from solid dispersions containing Kollidon® 12 PF because of the combination of erosion and diffusion mechanisms. The diffusion mechanisms were predominant in the initial phase of the experiment and the slow erosion was dissolution-controlling at the second stage of the dissolution. On the contrary, the tadalafil release rate from solid dispersions containing Kollidon® VA 64 was controlled solely by the erosion mechanism.
Keywords: solid dispersion; intrinsic dissolution rate; Weibull dissolution model; tadalafil; dissolution rate; Wood’s apparatus